Biomechanical evaluation of nursing cart handles using electromyography - Hsu, Ding Yang (Scientific reports, 2025)
The ergonomic design of emergency nursing carts is crucial for reducing musculoskeletal strain during clinical tasks. This study evaluates how different handle designs affect muscle activity and wrist joint angles, aiming to identify an optimal design that enhances comfort and reduces strain. Ten female participants performed straight-line pushing and turning tasks using five different nursing cart handle designs. Wrist joint angles—including flexion, extension, radial deviation, and ulnar deviation—were measured using a motion tracking system. Muscle activity in the biceps brachii, triceps brachii, extensor carpi radialis longus (ECR), and extensor carpi ulnaris (ECU) was recorded using electromyography (EMG). This study also discusses the limitations of EMG and motion tracking by comparing them with biomechanical measurement tools such as load cells, strain gauges, and subjective assessment tools like questionnaires and checklists. Data were analyzed for differences in muscle activation and wrist angle deviations across the handle designs. The study found that wrist joint angles varied significantly across handle designs. One of the tested handle designs minimized extreme wrist positions, leading to lower flexion and radial deviation angles compared to other designs. Wrist joint angles differed significantly between handle designs. Handle type C design effectively minimized extreme wrist positions, reducing flexion and radial deviation. EMG analysis showed that some handle designs significantly lowered muscle activity across all muscle groups, indicating reduced strain during straight and turning tasks. Regarding user comfort, participants rated certain handle designs as the most comfortable, aligning with their superior ergonomic performance based on objective measures. This study provides initial evidence that handle design may influence wrist joint angles, muscle activity, and perceived comfort during cart operation. A particular handle design, characterized by its ability to minimize musculoskeletal strain, offering a potential ergonomic improvement for emergency nursing carts, which warrants further investigation. The findings also highlight how improved ergonomic design can contribute to better healthcare efficiency and potentially enhance patient care by reducing fatigue-related errors.